2009
DOI: 10.1002/ptr.2836
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of water extract of a mushroom, Inonotus obliquus, against HT‐29 human colon cancer cells

Abstract: In the current study, it was demonstrated that the hot water extract of I. obliquus (IOWE) exerts inhibitory activity against the proliferation of human colon cancer cells (HT-29). The inhibitory effect of IOWE on the growth of HT-29 cancer cells was evaluated by treating cells with IOWE at concentrations of 0.25, 0.5 and 1.0 mg/mL for 24 or 48 h. The IOWE inhibited cell growth in a dose-dependent manner, and this inhibition was accompanied by apoptotic cell death. The maximum inhibitory effect (56%) was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 42 publications
(43 reference statements)
6
46
0
Order By: Relevance
“…When human colon cancer cells (HT-29) were treated by 1.0 mg/mL WEI for 48 h, the maximum inhibitory effect (56%) was observed, accompanying with down-regulation of Bcl-2 and up-regulation of Bax and caspase-3 (Lee et al, 2009). Among them, Bcl-2 can form ion channels in biological membranes, which then influence the permeability of intracellular membranes, and thus the mitochondrial contents released into the cytoplasm , potentially resulting in the activation of caspase-3 and thereby leading to the induction of apoptosis.…”
Section: Direct Participatiuon In the Cell Apoptosis Pathwaymentioning
confidence: 99%
“…When human colon cancer cells (HT-29) were treated by 1.0 mg/mL WEI for 48 h, the maximum inhibitory effect (56%) was observed, accompanying with down-regulation of Bcl-2 and up-regulation of Bax and caspase-3 (Lee et al, 2009). Among them, Bcl-2 can form ion channels in biological membranes, which then influence the permeability of intracellular membranes, and thus the mitochondrial contents released into the cytoplasm , potentially resulting in the activation of caspase-3 and thereby leading to the induction of apoptosis.…”
Section: Direct Participatiuon In the Cell Apoptosis Pathwaymentioning
confidence: 99%
“…Commercial patent medicine called Befungin is still used in cancer prevention and palliative treatment in this region (Lemiezek et al, 2011;Song et al, 2013). A decoction of sclerotia of I. obliquus is non-toxic to normal cells and several pharmacological studies have shown its antitumor activity against different malignancies, such as lung, breast, uterine, gastric, colon, and liver cancer as well as leukemia and melanoma (Lee et al, 2009;Lemiezek et al, 2011;Nomura et al, 2008;Won et al, 2011). I. obliquus is traditionally taken mainly in the form of a hot water extract; however, some significant differences can exist between the chemical compositions of hot water and ethanol extracts (Hu et al, 2009).…”
Section: Mushroomsmentioning
confidence: 99%
“…Triterpenoids such as inotodiol, lanosterol, and trametenolic acid are considered the main antitumor ingredients being able to induce growth inhibition, cell cycle arrest, and apoptosis in different cancer cells; however, the exact molecular mechanisms by which these effects occur are still not well understood (Chung et al, 2010;Du et al, 2011;Nomura et al, 2008;Youn et al, 2009;Zhong et al, 2011). Polysaccharides from I. obliquus can indirectly be involved in anticancer processes mainly via stimulating the immune system (Lee et al, 2009;Song et al, 2013). Immunotherapy through activation of a host immune system can indeed be a good alternative method for cancer control (Kim et al, 2006).…”
Section: Mushroomsmentioning
confidence: 99%
“…It has been demonstrated that many mushroom extraction products have been found to possess anticancer activity. 17) Therefore, searching for new anticancer and other medicinal substances from mushrooms and studying the medicinal value of these mushrooms has become a matter of great significance. In this work, new lanostane triterpene glycoside (Fomitoside-K), an active component of a medicinal mushroom, was extracted from the fruiting bodies of Fomitopsis nigra.…”
Section: Discussionmentioning
confidence: 99%